Complex Visceral Coupling During Central Sleep Apnea in Cats - Limanskaya, Alexandra V.; Busygina, Irina I.; Levichkina, Ekaterina V.; Pigarev, Ivan N. (Frontiers in Neuroscience, 2020)
Central sleep apnea is a sudden arrest of breathing during sleep caused by the central commands to the thoracoabdominal muscles. It is a widespread phenomenon in both healthy and diseased people, as well as in some animals. However, there is an ongoing debate whether it can be considered a pathological deviation of the respiratory function or an adaptive mechanism of an unclear function. We performed chronic recordings from 6 behaving cats over multiple sleep/wake cycles, which included EEG, ECG, eye movements, air flow, thoracic respiratory muscles movements, and in 4 cats combined that with the registration of myoelectric activity of stomach and duodenum. In these experiments, we observed frequent central cessations of breathing (for 5-13 seconds) during sleep. Each of sleep apnea episodes was accompanied by a stereotypical complex of somatic and visceral effects. Heart rate increased 3 – 5 seconds before the respiration arrest, and strongly decreased during the absence of respiration. Myoelectric activity of stomach and duodenum also often demonstrated strong suppression during apnea episodes. The general composition of the visceral effects was stable during all periods of observation (up to three years in one cat). We hypothesize that stereotypic coupling of activities in various visceral systems during episodes of central sleep apnea most likely reflects complex adaptive behavior rather than an isolated respiratory pathology, and discuss the probable function of this phenomenon.